IV international seminar on pedagogical practice (IV ISPP) (2021)
In the process of teaching and training students and new professionals, constructive actions and didactic spaces must be open where the teacher encourages the integral growth of their students, strengthening different technical/academic aspects and personal skills. With a good orientation and implementation of appropriate pedagogical practices, the teacher will have the ability to teach and create spaces to socialize, discuss and reflect about experiences that generate, not only the construction of new knowledge, but also the strengthening of principles and qualities in students, such as responsibility, honesty, equity, respect and the ability to reason to solve problems and conflicts. All this promotes the formation of human capital capable of confronting and solving different aspects and challenges that may be encountered in their training process and professional development. The present proceedings are part of the contributions of the participants in the IV International Seminar on Pedagogical Practice (IV ISPP) which was held from 26 to 27 August 2021, in the city of San José de Cúcuta, Colombia; congress was organized by the "Facultad de Educación, Artes y Humanidades" of the Universidad Francisco de Paula Santander, San José de Cúcuta, Colombia The main purpose of the IV ISPP was to create a space for training and academic and scientific cooperation for the construction, exchange, and development of research that aimed at the consolidation of innovation processes in education and pedagogical practices. This edition of the IV ISPP has emphasized the research, innovations, and reflections on didactics of natural sciences (mathematics, physics, chemistry, and biology) and its applications at both educational and scientific. The IV ISPP was attended by researchers, teachers of the basic, middle, and higher education, graduate and undergraduate students from Colombia, Argentina, Mexico, Chile, El Salvador, and Spain, who shared their contributions in the fields of teaching and applications of natural sciences (physics, mathematics, chemistry, biology, physics-mathematics, physical-chemistry, biophysics, Statistics, and education). On behalf of the organizing committee of the IV ISPP, we are extremely thankful to all authors and participants for providing their valuable contributions to this Proceedings volume as well as the reviewers for their constructive recommendations and criticism aiding to improve the presented articles. Likewise, we like to thank the Universidad Francisco de Paula Santander (UFPS), and the Foundation of Researchers in Materials Science and Technology (FORISTOM), and Red Iberoamericana de Pedagogia (REDIPE), for all the support technical and logistical received. Finally, the editor hopes that those interested in the area of pedagogical practice and didactics in natural sciences can enjoy this reading, of the volume of the Journal of Physics: Conference Series (JPCS), which reflects a wide variety of current issues.